Germination and Water Content of Cocoa Seeds After Storage Treatments - Indah Anita-Sari; Bayu Setyawan; Agung Wahyu Susilo (Indonesian Coffee and Cocoa Research Institute, 2018)
The challenge of providing cocoa seeds is the characteristic of recalcitrant seed, thus requiring storage techniques that can slow down the decline in seed viability in an effort to manage the distribution of cocoa seeds which depend to the time of demand and harvest. The research aimed to study the effect ofpackaging method for storage of cocoa seeds; the effect of shelf life and temperature to germination and water content of seeds, and the stability of seed germination at different age and storage temperature. The research was conducted at Kaliwining Experimental Station, Indonesian Coffee and Cocoa Research Institute, Jember, East Java. The research used complete randomized design with research design using split plot. The treatments consisted of packaging methods, storage temperature and storage life. Packaging methods consisted of two methods, i.e. vacuum methods and non vacuum methods. Storage temperature consisted of three treatments, i.e. 15OC, 25OC and 30OC. both of packaging and temperature treatments were stored at four shelf life treatment included 1 week, 2 weeks, 3 weeks, and 4 weeks. Each treatment was repeated with three replications and each treatment per replication consisted of 50 seeds. Data analysis used SAS 9.0 and stability analysis used R program and PB Tool. Water content of seeds, germination of seeds and number of seedy seeds were observed. The results showed that type of packaging and storage temperature effect to germination of cocoa seeds but did not effect to seeds water content. Storage of cocoa seeds by non-vacuum packaging showed a higher of germination compared to vacuum packaging in all temperature treatments. Storage with non vacuum packaging at a temperature 25OC showed a germination more than 85% for 2 weeks of shelf life, while storage of cocoa seeds at a temperature of 30OC had a germination of more than 85% for only 1 week shelf life. Storage of cocoa seed at 15OC showed the lowest of germination at treatment. Storage treatments did not show effect on water content of cocoa seeds.